Irrational man [videorecording (DVD)] - Allen, Woody, 1935-; Aidem, Betsy, 1957-; Phoenix, Joaquin; Stone, Emma, 1988-; Posey, Parker, 1968- (Sony Pictures Home Entertainment, 2016)
Philosophy professor Abe Lucas is at rock bottom emotionally, unable to find any meaning or joy in life. He feels that everything he₂s tried to do from political activism to teaching hasn't made any difference. Abe gets involved with two women: Rita Richards, a lonely professor who is unhappy in her marriage; and Jill Pollard, his best student, who becomes his closest friend. Pure chance changes everything when Abe and Jill overhear a stranger's conversation and become drawn in.